MODELING AND SIMULATION OF THERMOELECTRIC PLANT OF COMBINED CYCLES AND ITS ENVIRONMENTAL IMPACT - Mitre, J. F.; Lacerda, A. I.; de Lacerda, R. F. (Revista de Engenharia Térmica, 2005)
The impact any power plant has upon the environment must be minimized as much as possible. Due to its high efficiency, low emission levels and low cooling requirements, combined cycle plants are considered to be environmentally friendly. This study evaluates the effect of operational conditions on pollutants (CO, CO2, SOx, NOx) emissions levels, waste-heat and wastewater of a combined-cycle natural gas and steam power plant. The HYSYS process simulation was used for modelling and simulation. The study clearly shows that the absolute quantity of pollutants emitted is high. Also, it was possible to verify that the unit operate in the condition of minimal emissions regarding the maximum possible, and thus a reduction or elimination of such pollutants is not possible.